2020
DOI: 10.1017/jfm.2020.877
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic shock impingement on a heated flat plate at Mach 7 flight enthalpy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
5
12
0
Order By: Relevance
“…The Reynolds number at this location is 2.16 × 10 6 , consistent with the transition Reynolds number of 2 × 10 6 developed from previous flat plate studies in T4 (Mee 2002). The heat-transfer measurements from both conditions indicate that the boundary layers are laminar upstream of the expected shock impingement locations (x ≈ 260 mm), confirmed in the heated SBLI work (Chang et al 2021).…”
Section: Flow Establishment and Mean Surface Propertiessupporting
confidence: 87%
See 3 more Smart Citations
“…The Reynolds number at this location is 2.16 × 10 6 , consistent with the transition Reynolds number of 2 × 10 6 developed from previous flat plate studies in T4 (Mee 2002). The heat-transfer measurements from both conditions indicate that the boundary layers are laminar upstream of the expected shock impingement locations (x ≈ 260 mm), confirmed in the heated SBLI work (Chang et al 2021).…”
Section: Flow Establishment and Mean Surface Propertiessupporting
confidence: 87%
“…Therefore, this study aims to fill this gap with detailed surface data from an impinging SBLI experiment conducted in the University of Queensland's T4 Stalker Tube. In line with this, the present authors examined the effect of high wall temperatures in impinging shock-induced flow separation on a heated flat plate (Chang et al 2020(Chang et al , 2021. One shortcoming of the hot-wall studies was that the model lacked surface instrumentation due to its high wall temperature.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another correlation based on Katzer (1989) has recently been used by Chang et al. (2021) for an impinging shock SBLI on a heated flat plate in a Mach 7 high-enthalpy hypersonic flow. They found that the correlation of Bleilebens & Olivier (2006) for a heated compression ramp at hypersonic Mach numbers was not quite applicable to an impinging shock SBLI.…”
Section: Introductionmentioning
confidence: 99%